Conceptual Development of Urban Super-blocks Model in Urban Planning Based on Content Analysis Method - Hafez Mahdnejad (توسعه پایدار شهری)
The superblock model is one of the urban models that have been proposed in response to climate change and expansion of walkability. Based on this, current research purpose is conceptual development of urban superblocks model for the use of urban planners and policy makers of the country.The current research is applied-developmental in terms of purpose and descriptive-analytical in terms of data collection method. The current research method is qualitative and based on content analysis. The statistical community includes various sources including articles, books, and theses, which were used to select the sources using available and snowball sampling methods. The sample size includes 35 sources consisting of articles, books and theses. The statistical community includes various sources such as articles, books, and theses, which have been used to select sources using available and snowball sampling methods. The sample size includes 35 sources consisting of articles, books and theses. According to the research results, in terms of typology, 74% of research sources are related to articles. In terms of time, the largest amount of research resources is related to the years 2022 and 2023, which is equivalent to 49% of the resources. The most sources are from Science Direct and MDPI, ProQuest and ResearchGate databases, which is equivalent to 74% of research sources. The approach of most sources is quantitative and qualitative (71 percent). The most methods of data collection are related to field studies, literature review, observation, interviews, spatial data and document analysis, which account for 84% of the research resources. The research method of most of the sources includes explanation, case study, descriptive-analytical method, which account for 80% of the sources. Based on the analysis and synthesis of the findings, 101 open codes have been identified regarding the unique characteristics of urban superblocks, which have been classified into 31 core codes. Axial codes in six selected codes are classified including background conditions (superblock and mini-block environment), causal conditions (field of urban action, land use and urban morphology, urban function, urban complexity, biodiversity and urban green, metabolic efficiency , social unity, human-centered street, complete streets, healthy streets and sustainable streets), mediating conditions (good urban governance and mixed use), central category (biological and physiological needs, security needs, belonging needs, respect needs, cognitive needs, aesthetic needs and self-fulfillment needs), strategies (green space redesign, space reassignment and restrictions and active transportation) and consequences (environmental improvement, traffic reduction, air pollution reduction, social cohesion, health promotion, economic). The selected codes form the conceptual model of the urban superblock.